The life of the Prophet Muhammad S.A.W.W - Azzam, Leila (Lahore : Ilqa publications, 2020)
A unique and meticulous exploration of the life of Prophet Muhammad (PBUH). This comprehensive trilogy is not just a chronological account but a profound reflection on the purposeful and transformative episodes of the Prophet's life.
Keywords: Islam - Seerat